Roman and late antique wine production in the eastern Mediterranean : a comparative archaeological study at Antiochia ad Cragum (Turkey) and Delos (Greece) - Dodd, Emlyn K. (Archaeopress Roman archaeology, 2020)
Wine was an ever-present commodity that permeated the Mediterranean throughout antiquity. This book analyses the viticulture of two settlements, Antiochia ad Cragum and Delos, using results stemming from surface survey and excavation to assess their potential integration within the now well-known agricultural boom of the 5th-7th centuries AD.